Performance of Banks under Financial Inclusion and the Reasons for Slow ProgressA Study of Rural Area of Udaipur District in Rajasthan - Gaurav Suwalka (Indian Journal of Extension Education, 2017)
Financial Inclusion assumes paramount importance in our country where 65 percent population lives in rural area, engage in agriculture and allied activities with large numbers of them are poor. The aim of Financial Inclusion is to promote sustainable development and generate employment for a vast majority of population especially in the rural area. The banks’ role is vital in mobilizing savings and providing credit in rural area. Though our country’s economy is growing at around 7 percent, the growth is not inclusive of rural people. Majority of rural people are financially excluded (Kainth, 2010). The performance of banks in rural area is not satisfactory. The present study was conducted in rural area of Udaipur District in Rajasthan with the aim of finding out the reasons for poor performance under Financial Inclusion. Sample size of 120 rural people and 12 bankers were kept as respondents. Many reasons were opined by the rural people and bankers. The important ones are not attending to the rural people, not interacting with them for lack of time, not financing the needy rural poor, dormancy of accounts, lack of infrastructure, distance from branches, illiteracy and frequent need of credit by rural people.